FUNGSI EVALUASI KELEMBAGAAN DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH IBTIDAIYAH DI KOTA BENGKULU - Khairiah, Khairiah; Irsal, Irsal (UIN Fatmawati Sukarno Bengkulu, 2024)
ABSTRACTThe evaluation of madrasah education institutions has not functioned properly, causing gaps in improving the quality of madrasah ibtidaiyah education. The purpose of this study is to evaluate and analyze the function of institutional evaluation in improving the quality of madrasah ibtidaiyah education in Bengkulu City. Using descriptive qualitative methods with a gap evaluation model approach, namely the gap between planning and implementation, the gap in capability standards set with reality, and the gap in achieving goals with planning. The results showed that the gap between planning and implementation, the gap in ability standards set with reality, and the gap in achieving goals with planning, and the results of the analysis of the institutional evaluation function in improving the quality of madrasah ibtidaiyah education showed that the evaluation serves to improve the program and also helps teachers, employees and students in producing learning and work effectively and quality including input, educational processes and outputs. So it can be concluded that the institutional evaluation function can improve the quality of madrasah ibtidaiyah education in the form of continuous assessment, monitor the learning process and progress of students and can increase learning effectiveness, and have a positive effect on improving the quality of madrasah ibtidaiyah education in Indonesia. Thus, it can be suggested, if you want to improve the quality of madrasah ibtidaiyah education, then improve the function of institutional evaluation. Keywords: Evaluation Function, Institutional, Quality of Education, Madrasah Ibtidaiyah.